Geomorphological and sedimentary traces of historical and modern exceptional flooding events in a dry valley of the Andean Precordillera (Tarapacá Region, N Chile) - Seeger, Katharina; May, Simon Matthias; Brill, Dominik; Herbrecht, Marina; Hoffmeister, Dirk; Quandt, Dietmar; Stoll, Alexandra; Rhein, Alexander; Keiser, Maximilian; Wolf, Dennis; Bubenzer, Olaf (Geomorphology, 2024)
While palaeoenvironmental records of the Atacama Desert and Andean Altiplano region document wet conditions related to the Central Andean Pluvial Events in the late Pleistocene/early Holocene, the spatio-temporal pattern of mid- to late Holocene or even historical climatic fluctuations so far remains ambiguous with only few records documenting the climatic conditions over the last centuries. Uncertainties remain particularly for latitudes around 20°S and for the Andean Precordillera in general. These need to be addressed in order to decipher the spatial extent and potential linkage of hydroclimatic changes observed in palaeoenvironmental records from the Andes and the Pampa del Tamarugal basin from ∼18 to ∼25°S. This study aims to shed light on historical flooding activity in a dry (ephemeral) valley east of Pica town in the lower Andean Precordillera (Tarapacá Region, N Chile), which is characterised by steep, slump-dominated slopes with aeolian sediments and generally short sediment transport distances. Combined remote sensing, sedimentological and chronostratigraphical investigations were applied to study the geomorphological and sedimentary impact of flood-related morphodynamics on the valley and the sedimentary record, using the recent February 2019 flooding event as a reference. Our methodological approach allowed for the differentiation of flood-related from aeolian deposits. Three facies of flood-type deposits were identified, namely slackwater, channel-type and levee-type deposits. While the February 2019 flooding constitutes an unprecedented event for the era of satellite imagery since 1966, past flooding activity in the valley, comparable to the 2019 event, was reconstructed to have occurred at ∼300 years ago and during the late 19th to early 20th century. The spatio-temporal pattern of flooding activity with a multi-decadal to centennial cyclicity derived from this study seems to be synchronous to hydroclimatic fluctuations reconstructed from other palaeo-records in the Altiplano and proves the sensitivity of the Precordilleran valleys to palaeoenvironmental and palaeoclimatic fluctuations in the broader area.